Identifikasi Fungi Endofit Pada Tanaman Binahong (Andredera cordifolia) Serta Potensinya Sebagai Antibakteri Terhadap Staphylococcus aureus: Identification of Endophytic Fungi in Binahong Plants (Andredera cordifolia) and Their Potential as Antibacterials Against Staphylococcus aureus - Hamtini; Ghani Nurfaizi; Aminah Aminah; Nining Kurniati; Mardyana Nizar (LPPM Universitas Abdurrab, 2025)
Indonesia is known as a mega biodiversity country rich in biodiversity, animals and their ecosystems. The parts of the binahong plant (Andredera cordifolia) that can be utilized come from flowers, leaves, stems, roots, and tubers that have metabolite compounds such as flavonoids, tannins, alkaloids, terpenoids and saponins. This can be used as a basis for utilizing binahong leaves from which endophytic fungi are taken to determine the potential for secondary metabolites from endophytic fungi in binahong leaves by means of isolation, identification and antibacterial potential against Staphylococcus aureus bacteria. The purpose of the study was to determine the presence or absence of endophytic fungi in binahong plants and to determine their potential as antibacterials in endophytic fungi isolated from binahong plants against Staphylococcus aureus. The methods in this study were isolation, purification of endophytic fungi, preparation of Staphylococcus aureus test bacteria, antibacterial test using the agar diffusion method. The results showed that there were 5 isolates of endophytic fungi, with isolate codes AK. H, AK. M, BT 1.1, BT 2.1, and DA 1, microscopically the fungi obtained were Penicillium sp, and Mucor sp. And have the ability to inhibit the growth of Staphylococcus aureus bacteria included in the strong category, with an average inhibition zone of 20 mm, 20.5 mm, 15.5 mm, 21 mm, 22.5 mm respectively. The conclusion of this study is that endophytic fungal isolates in binahong plants have the potential as antibacterials against Staphylococcus aureus.